Cerebral edema after ischemic stroke: Pathophysiology and underlying mechanisms - Gu, Yuhang; Zhou, Chen; Piao, Zhe; Yuan, Honghua; Jiang, Huimin; Wei, Huimin; Zhou, Yifan; Nan, Guangxian; Ji, Xunming (Frontiers in Neuroscience, 2022)
Ischemic stroke is associated with increasing morbidity and has become the main cause of death and disability worldwide. Cerebral edema is a serious complication arising from ischemic stroke. It causes an increase in intracranial pressure, rapid deterioration of neurological symptoms, and formation of cerebral hernia, and is an important risk factor for adverse outcomes after stroke. To date, the detailed mechanism of cerebral edema after stroke remains unclear. This limits advances in prevention and treatment strategies as well as drug development. This review discusses the classification and pathological characteristics of cerebral edema, the possible relationship of the development of cerebral edema after ischemic stroke with aquaporin 4, the SUR1-TRPM4 channel, matrix metalloproteinase 9, microRNA, cerebral venous reflux, inflammatory reactions, and cerebral ischemia/reperfusion injury. It also summarizes research on new therapeutic drugs for post-stroke cerebral edema. Thus, this review provides a reference for further studies and for clinical treatment of cerebral edema after ischemic stroke.